2015
DOI: 10.18280/ijht.330109
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy and Thermocapillary Driven Flows in an Open Cavity With Bottom Heating and Symmetrical Cooling From Sides

Abstract: In this study, the effect of thermocapillary and buoyancy driven flows in an open cavity filled with fluid is numerically examined. A physical configuration is encountered where a constant heating element at the bottom wall and cooled from the sidewalls while the top wall can be considered free surface. The length of the heat source is varied from 20 to 100% of t he total length of the bottom wall and remaining parts are adiabatic. The governing equations are discretized by finite volume method with power law … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The other parameters are as follows: electrode-plate mass ratio R'=0.1, plate thickness 2h=200 m, electrodes radii R 0 =620 m, R 1 =720 m and R 2 =1,500 m. The trapped modes are the interest modes and found in the narrow frequency interval determined by Eq (14). By this equation, it is determined that Figure 2.…”
Section: Numerical Simulation and Results Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…The other parameters are as follows: electrode-plate mass ratio R'=0.1, plate thickness 2h=200 m, electrodes radii R 0 =620 m, R 1 =720 m and R 2 =1,500 m. The trapped modes are the interest modes and found in the narrow frequency interval determined by Eq (14). By this equation, it is determined that Figure 2.…”
Section: Numerical Simulation and Results Analysismentioning
confidence: 98%
“…Since a 1 is about half of a 2 , the electrode size varied more violently than the plate thickness with the same temperature change. Based on these values,   and   were calculated by Eq (14). In each case, the two trapped modes of interest were found in the frequency interval.…”
Section: Numerical Simulation and Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Thermocapillary convection has received a considerable attention in recent years since it plays the key role in a variety of industrial processes such as crystal growth [1], thin film coating [2], laser welding [3], cooling of electronic devices [4], glass manufacturing and some chemical processing [5]. Initially, researchers conducted extensive research on the stability of thermocapillary convection without phase change interfaces [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that an increase in Rayleigh number and heat source length enhances the heat transfer inside the enclosure. Thereafter, further studies have been conducted to analyze different effects such as heat source position, aspect ratio, inclination of the enclosure and others may be found in [21][22][23][24][25][26][27][28][29]. For the second category when the heat source produces a uniform heat flux, Sharif and Mohammad [30] have numerically studied the same configuration as [20], where the heat source at the lower wall has been replaced with a uniform heat flux source.…”
Section: Introductionmentioning
confidence: 99%